Perception of organizational politics and the effect of authenticity and affective commitment on deviance and task performance in contact centers - Rodrigues, Ana Marta Braga (2016)
This study aimed to understand employees’ reactions to organizational politics in Contact Centers. Drawing from a sample of 187 supervisor-employee dyads, we studied the relationship between employees’ perceptions of organizational politics and supervisor-rated task performance and deviance, and mediation effects by authenticity at work and affective commitment. Results indicate that workers tend to react to workplace politics with deviant behavior and worse task performance. We found that the relationship between perceived politics and task performance was mediated by authenticity. The relationship between perceived politics and supervisor-rated deviance was mediated by affective commitment to the organization. Implications for management are discussed.